Implementasi Technological Pedagogical and Content Knowledge dalam Mata Kuliah Inovasi Pembelajaran: Analisis Hasil Belajar Mahasiswa - Sri Astuti Iriyani; Elyakim Nova Supriyedi Patty; Nining Anggeraini (MASALIQ, 2025)
The limited number of empirical studies on the implementation of Technological Pedagogical and Content Knowledge (TPACK) in higher education highlights the need for further investigation, given its potential to enhance instructional effectiveness and students' mastery of course material. This study aims to analyze the application of TPACK-based learning in the Inovasi Pembelajaran course and to evaluate its impact on lecturer activity, student participation, and learning outcomes. The method employed was Classroom Action Research using the John Eliot model, involving 24 fifth-semester students from the Information Technology Education program selected through purposive sampling. Data were collected through observations of lecturer and student activities, as well as learning outcome tests, and analyzed descriptively to identify improvement trends across three cycles. The results show significant increases across all indicators: lecturer activity scores rose from 53.20 in Cycle I to 82.60 in Cycle III; student activity from 57.40 to 88.10; and learning outcomes from 60.20 to 87.50. These findings indicate that TPACK is an effective conceptual and practical framework for integrating technology, pedagogy, and content synergistically. The study concludes that systematic implementation of TPACK enhances instructional quality, lecturer competence, and student learning outcomes. The implications include theoretical contributions to the growing body of literature on TPACK integration in higher education, as well as practical recommendations for lecturers to design adaptive, interactive, and student-centered learning.